Mapping strategic knowledge - Huff, Anne Sigismund; Jenkins, Mark, 1959- (SAGE, 2002)
This book outlines a number of different tools for mapping strategic knowledge, and thus making knowledge more accessible. Anne Huff and Mark Jenkins have brought leading academics together to: * illustrate the contribution of knowledge mapping to central issues in strategy and organization theory * provide informed analysis and theory * consider the contribution of these studies to management practice * address practical theoretical and methodological limitations of these tools, including several software tools now available to facilitate mapping Each section of the book provides a table, whi.